The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jpcc.8b06991
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism behind the Unusually High Conductivities of High Concentrated Sodium Ion Glyme-Based Electrolytes

Abstract: New highly concentrated electrolytes based on ether solvents were developed for sodium electrochemical cells. The investigated electrolytes use sodium triflate and glycol diether oligomers of different length to form the electrolyte. These electrolytes present conductivities that increase as a function of concentration even when the electrolyte is composed of a majority of ion pairs and aggregates. Correlation analysis between the electrolyte speciation and conductivity suggests the presence of two distinct me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 53 publications
4
38
0
1
Order By: Relevance
“…Two mechanisms of charge transport, diffusion of free ions and hopping between ion pairs, were postulated for concentrated Na electrolytes in ether solvents. 29 A similar effect of residence times decreasing with increasing salt concentration was also reported for sodium salt solutions in acetonitrile 45 and attributed to the transport mechanism.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Two mechanisms of charge transport, diffusion of free ions and hopping between ion pairs, were postulated for concentrated Na electrolytes in ether solvents. 29 A similar effect of residence times decreasing with increasing salt concentration was also reported for sodium salt solutions in acetonitrile 45 and attributed to the transport mechanism.…”
Section: Resultssupporting
confidence: 66%
“…However, at high salt concentration, an alternative mechanism of ion hopping between aggregates may become operative; 29 , 43 its effectiveness may be dependent on the solvent. 29 In this work, we showed that the interplay between ion concentration and mobility may be also affected by the anion of the salt, changing the degree of correlations. Through the analysis of contributions to the total conductivity, we found that ion–ion correlations in NaTFSI solutions are much more important than in NaFSI electrolytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A adição de moléculas de PEO como solvente é amplamente utilizada em eletrólitos de metais alcalinos e, consequentemente, diversos estudos empregam diferentes tamanhos de PEO [36][37][38]40,41,[228][229][230][231] 187 Apesar disso, a maioria das simulações atomísticas reportam micelas de DPC ligeiramente elipsoidal 183,188,234 . No trabalho de Abel et al 183 Tabela 9.…”
Section: Misturas Ternárias [Emim] + [B(cn)4] -| Sais De Na + /K + | unclassified